2020
DOI: 10.1186/s13256-020-02395-9
|View full text |Cite
|
Sign up to set email alerts
|

Sacrococcygeal teratoma with preterm delivery: a case report

Abstract: Background: Sacrococcygeal teratoma is one of the most frequently prenatally diagnosed neoplasias. Obstetric ultrasound has a role in the diagnosis and management of these tumors during pregnancy. In this report, we describe a multidisciplinary approach in a case of a patient with sacrococcygeal teratomas and preterm delivery, as well as postnatal outcomes. Case presentation: A 26-year-old Caucasian woman at 20.3 weeks of gestation with a normal gestational course and no relevant medical or surgical history wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…9 Teratomas can be asymptomatic or may cause rectal or bladder obstruction, related to tumor growth. 7 Rapid growth of the mass may cause pressure on adjacent organs, such as rectum or bladder resulting in organ dysfunction (e.g., fecal or urine incontinence). 12 Several parameters can be used to predict the prognosis of SCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Teratomas can be asymptomatic or may cause rectal or bladder obstruction, related to tumor growth. 7 Rapid growth of the mass may cause pressure on adjacent organs, such as rectum or bladder resulting in organ dysfunction (e.g., fecal or urine incontinence). 12 Several parameters can be used to predict the prognosis of SCT.…”
Section: Discussionmentioning
confidence: 99%
“…6 A 3-year postoperative surveillance should include serum AFP, beta-human chorionic gonadotropin, and physical examination, every 3 to 6 months, as well as assessing the risk for surgical complications, recurrence, residual tumor, and malignancy. 7,9,12 Long-term surgical complications have been reported, including urologic and anorectal dysfunction with an incidence of 33% and 29%, respectively. 5 This case report discussion has the limitation that sources published in English were used for references, which may have resulted in missing information and or knowledge gaps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from this review highlight a low percentage of studies based on polyhydramnios associated with GDM. Baro et al [ 44 ] reported a case of a pregnancy complicated with GDM but also with an associated fetal abnormality, sacrococcygeal teratoma. Comparing this case report with ours, there are some similarities, namely, the good neonatal outcome and the necessity of cesarean delivery due to abnormal fetal heart rate.…”
Section: Discussionmentioning
confidence: 99%